A new semisynthetic cardenolide analog 3β-[2-(1-amantadine)-1-on-ethylamine]-digitoxigenin (AMANTADIG) affects G2/M cell cycle arrest and miRNA expression profiles and enhances proapoptotic survivin-2B expression in renal cell carcinoma cell lines - Nolte, Elke; Wach, Sven; Silva, Izabella Thais; Lukat, Sabine; Ekici, Arif Bülent; Munkert, Jennifer; Müller-Uri, Frieder; Kreis, Wolfgang; Simões, Cláudia M. O.; Vera González, Julio; Wullich, Bernd; Taubert, Helge; et al. (Oncotarget, 2017)
EVALuna2:9377
Keywords: Cardiac glycoside analog; Cell cycle; 3β-[2-(1-amantadine)-1-on-ethylamine]-digitoxigenin; Human renal cell carcinoma cells; MiRNA

Comparative microRNA Profiling of Prostate Carcinomas with Increasing Tumor Stage by Deep Sequencing - Hart, Martin; Nolte, Elke; Wach, Sven; Szczyrba, Jaroslaw; Taubert, Helge; Rau, Tilman; Hartmann, Arndt; Graesser, Friedrich A.; Wullich, Bernd (Molecular Cancer Research, 2014)
MicroRNAs (miRNA) posttranscriptionally regulate gene expression and are important in tumorigenesis. Previous deep sequencing identified the miRNA profile of prostate carcinoma versus nonmalignant prostate tissue. Here, we generated miRNA expression profiles of prostate carcinoma by deep sequencing, with increasing tumor stage relative to corresponding nonmalignant and healthy prostate tissue, and detected clearly changed miRNA expression patterns. The miRNA profiles of the healthy and nonmalignant tissues were consistent with our previous findings, indicating a high fidelity of the method employed. In the tumors, quantitative real-time PCR (qRT-PCR) analysis of 40 paired samples of prostate carcinoma versus normal tissue revealed significant upregulation of miR-20a, miR-148a, miR-200b, and miR-375 and downregulation of miR-143 and miR-145. Hereby, miR-375 increased from normal to organ-confined tumors (pT2 pN0), slightly decreased in tumors with extracapsular growth (pT3 pN0), but was then expressed again at higher levels in lymph node metastasizing (pN1) tumors. The sequencing data for miR-375 were confirmed by Northern blotting and qRT-PCR. The regulation for other selected miRNAs could, however, not be confirmed by qRT-PCR in individual tumor stages. MiR-200b, in addition to miR-200c and miR-375 reduced the expression of SEC23A. Interestingly, miR-375, found by sequencing in pT2 upregulated by us and others in tumor versus normal tissue, and miR-15a, found by sequencing in pT2 and pT3 and in the metastasizing tumors, target the phosphatases PHLPP1 and PHLPP2, respectively. PHLPP1 and PHLPP2 dephosphorylate members of the AKT family of signal transducers, thereby inhibiting cell growth. Coexpression of miR-15a and miR-375 resulted in downregulation of PHLPP1/2 and strongly increased prostate carcinoma cell growth. Implications: These genomic data reveal relevant miRNAs in prostate cancer that may have biomarker and therapeutic potential. Mol Cancer Res; 12(2); 250-63. ©2013 AACR.
EVALuna2:6552

Cytotoxicity of AMANTADIG - a semisynthetic digitoxigenin derivative - alone and in combination with docetaxel in human hormone-refractory prostate cancer cells and its effect on Na+/K+ -ATPase inhibition. - Silva, Izabella Thais; Munkert, Jennifer; Nolte, Elke; Schneider, Naira F. Z.; Rocha, Sayonarah C.; Ramos, Ana Carolina Pacheco; Kreis, Wolfgang; Braga, Fernão Castro; De Padua, Rodrigo Maia; Taranto, Alex G.; Cortes, Vanessa Faria; Barbosa, Leandro A.; et al. (Biomedicine & Pharmacotherapy, 2018)
Keywords: Prostate cancer; AMANTADIG; docetaxel; synergistic effects; Na+/K+ -ATPase; docking studies

Piwil 2 expression is correlated with disease-specific and progression-free survival of chemotherapy-treated bladder cancer patients - Taubert, Helge; Wach, Sven; Jung, Rudolf; Pugia, Michael; Keck, Bastian; Bertz, Simone; Nolte, Elke; Stoehr, Robert; Lehmann, Jan; Ohlmann, Carsten-H; Stöckle, Michael; Wullich, Bernd; et al. (Molecular Medicine, 2015)
Piwi-like 2 (Piwil 2) belongs to the family of Argonaute genes/proteins. The expression of Piwil 2 is associated with stem cells. A role in tumorigenesis and/or tumor progression is proposed for different cancers but not yet for bladder cancer (BCa). We investigated the Piwil 2 expression by immunohistochemistry in a cohort of 202 BCa patients treated by cystectomy and adjuvant chemotherapy. The association between Piwil 2 expression and disease-specific (DSS) or progression-free survival (PFS) was calculated using Kaplan Meier analyses and univariate/multivariate Cox's regression hazard models.In a multivariate Cox's regression, Piwil 2 expression, either in the cytoplasm or the nucleus, was significantly associated with DSS and PFS. A weak cytoplasmic staining pattern was associated with poor DSS and tumor progression (RR=2.7; P=0.004 and RR=2.4; P=0.027). Likewise,, absent nuclear Piwil 2 immunoreactivity was associated with poor DSS and tumor progression (RR=2.3; P=0.023 and RR=2.2; P=0.022). BCa patients whose tumors exhibited a combination of weak cytoplasmic and absent nuclear immunoreactivity had a 6-fold increased risk of tumor-related death (P=0.005) compared to patients with strong expression. Considering only patients with high grade G3 tumors, a 7.8-fold risk of tumor-associated death and a 3.6-fold risk of tumor progression were detected independently of the histologic tumor subtype or the chemotherapy regimen. In summary, a combination of weak cytoplasmic and absent nuclear expression of Piwil 2 is significantly associated with an increased risk of DSS and tumor progression. This implicates that Piwil 2 could be a valuable prognostic marker for high-risk BCa patients.
EVALuna2:6705

Production of the Cytotoxic Cardenolide Glucoevatromonoside by Semisynthesis and Biotransformation of Evatromonoside by a Digitalis lanata Cell Culture. - Munkert, Jennifer; Santiago Franco, Marina; Nolte, Elke; Silva, Izabella Thais; Oliveira Castilho, Rachel; Ottoni, Flaviano Melo; Schneider, Naira F. Z.; Oliveira, Mônica C.; Taubert, Helge; Bauer, Walter; Andrade, Saulo F.; Alves, Ricardo J.; et al. (Planta medica, 2017)
Recent studies demonstrate that cardiac glycosides, known to inhibit Na(+)/K(+)-ATPase in humans, have increased susceptibility to cancer cells that can be used in tumor therapy. One of the most promising candidates identified so far is glucoevatromonoside, which can be isolated from the endangered species Digitalis mariana ssp. heywoodii. Due to its complex structure, glucoevatromonoside cannot be obtained economically by total chemical synthesis. Here we describe two methods for glucoevatromonoside production, both using evatromonoside obtained by chemical degradation of digitoxin as the precursor. 1) Catalyst-controlled, regioselective glycosylation of evatromonoside to glucoevatromonoside using 2,3,4,6-tetra-O-acetyl-α-D-glucopyranosyl bromide as the sugar donor and 2-aminoethyldiphenylborinate as the catalyst resulted in an overall 30 % yield. 2) Biotransformation of evatromonoside using Digitalis lanata plant cell suspension cultures was less efficient and resulted only in an overall 18 % pure product. Structural proof of products has been provided by extensive NMR data. Glucoevatromonoside and its non-natural 1-3 linked isomer neo-glucoevatromonoside obtained by semisynthesis were evaluated against renal cell carcinoma and prostate cancer cell lines.

The new semisynthetic cardenolide analog 3β-[2-(1-amantadine)-1-on-ethylamine]-digitoxigenin (AMANTADIG) efficiently suppresses cell growth in human leukemia and urologic tumor cell lines - Nolte, Elke; Sobel, Anna; Wach, Sven; Hertlein, Heidi; Ebert, Nadja; Müller-Uri, Frieder; Slany, Robert; Taubert, Helge; Wullich, Bernd; Kreis, Wolfgang (Anticancer Research, 2015)
Background/Aim: The use of cardenolides in the treatment of cardiac insufficiency is well-established. However, the potential of cardenolides in tumor therapy has not been comprehensively studied. The aim of the present study was to characterize the cytotoxic effects of the new semisynthetic cardenolide analog AMANTADIG (3β-[2-(1-amantadine)-1- on-ethylamine]-digitoxigenin), and the cardenolide digitoxin on leukemia and urological tumor cell lines. Materials and Methods: The anti-proliferative effects of AMANTADIG and digitoxin on leukemia and urological cancer cell lines were analyzed using (3-(4,5-Dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide) tetrazolium reduction viability assay. Results: AMANTADIG and digitoxin exhibited antiproliferative activities against the leukemia cell lines in the low nanomolar range. The prostate cancer and renal cell carcinoma cell lines were equally sensitive to AMANTADIG and digitoxin, however, the leukemia cell lines were more sensitive to both cardenolides. Conclusion: The new cardenolide analog AMANTADIG appears effective in cell growth inhibition of leukemia and urological tumor cell lines.
Keywords: 3β-[2-(1-Amantadine)-1-on-ethylamine]-digitoxigenin; AMANTADIG; Cardenolide analog; Human leukemia cells; Human urological cancer cells; Porcine cerebral cortex Na+/K+-ATPase